Application of the Transformational Leadership Style at the BKKBN office in South Sulawesi Province - Wader, Noris; Darwis, Muhammad; Salam, Rudi; Baharuddin, Aris (Universitas Negeri Makassar, 2017)
The research objective is to determine the application of the Transformational Leadership Style at the National Population and Family Planning Agency (Indonesia: Badan Kependudukan dan Keluarga Berencana Nasional / BKKBN) in South Sulawesi Province. The design of this research is quantitative descriptive research. Researchers took 35% of the population of 110 people using random sampling techniques, so the research sample numbered 38 people. Techniques for getting data are: observation, interview, questionnaire and documentation. The data analysis technique used in this research is descriptive analysis technique. The results of the study show that the application of the Transformational Leadership Style runs well seen from various indicators namely: Charismatic, Intellectual, Stimulation, and Individual Consideration.